Synthesis, Characterization and Broad-Spectrum Antibacterial Activity of Zinc Oxide Nanoparticles against Gram–Positive and Gram-Negative Bacteria - Keerthika, V.; Ananth, A.; Rajan, M.R. (Chemical and Materials Sciences: Research Findings Vol. 3, 2025)
Zinc oxide nanoparticles (ZnO-NPs) have received significant attention in recent years due to their versatile applications in sunscreen products, cosmetics, pigments, industrial coatings, plastic additives, semiconductors, textiles, and effective antibacterial agents. Due to numerous applications of nanoparticles, research related to preparation and the properties of nanoparticles has become more attention in the past several years. This study deals with the synthesis of zinc oxide nanoparticles and evaluating their antibacterial activity. Zinc oxide nanoparticles were synthesized by a chemical method and characterized by various analytical techniques such as UV-visible spectroscopy, SEM-EDX, XRD, and FTIR. X-ray diffraction and SEM analysis confirmed the formation of well-dispersed zinc oxide nanoparticles with average particle size 22 nm as well as revealed their spherical structure. Using the agar well diffusion technique of the study, chemically synthesized nanoparticles were revealed to have antibacterial activity against the bacterial strains Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus. There is a noticeable rise in ZnO nanoparticles' bioactivity because of their tiny size and greater surface area-to-volume ratio. This study demonstrates that ZnO NPs are a potential antibacterial agent that can combat both Gram-positive and Gram-negative bacteria. The antibacterial properties of ZnO nanoparticles make it feasible to be utilized as an antibacterial agent in products like mouthwashes, lotions, and ointments. Nanoparticles can also serve as substrates in medical devices to stop germs from sticking, spreading, and reproducing. Therefore, this work has significant theoretical and practical implications for further in-depth research.